Taste for money - an innovation by Nigerian women - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Thousands of West African women earn a cash income by making daddawa (a protein-rich seasoning made from locust beans and used for soups and stews) in low-capital input, small scale enterprises at home, and selling it in local markets. Now Nigerian...